(3bUjOI aj GdfaS GdfGWbIs ((3MSjf eYeGQR s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg abO EdJeS efi HYV ENhGfi GdcQGe hNdGfi GdTgGe TQM bUjOI GdQFjS hgPg GdbUjOI GdLdjdI gHWJ Edjc ef GdeMd GdCQaY hQbGA PGJ JaQR hJefY s
(3BNQgG (B:s
(3EPG EfaUdJ Yfg cCfgG eG EJUdJ Hg cGdHhb heeJfY HhLhOg GdfGS hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B32s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQNjgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs